(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India is an agriculturally based country where different personalities belong to various communities and coexist. The majority of Indian farmers are small-scale producers, and due to the high cost of sowing equipment, the farmer would be unable to employ such devices. Thus, the equipment on the market is largely tractors, robots, and so on. These devices are useful and inexpensive for large-scale farmers, but not for small-scale farmers. As a result, small-scale farmers choose conventional methods to save the costs of fuels necessary to power such devices, as fuel prices rise in the worldwide market. The research is carried out to comprehend the operation of various machines on the market, as well as the operation of a device with various seed samples from various seasons. As a result, there is a requirement for machinery that is inexpensive, simple to run, requires little maintenance, and can do numerous seed sowing procedures simultaneously to save the farmer money on labor. The goal of the device is to improve farming more comfortable for local producers by increasing production while decreasing labor costs.